On the Peculiarities of the Artistic Form of the Lezgin Folk Proverbs and Sayings (Proceedings of Southern Federal University. Philology, 2020)
National proverbs and sayings of Lezgins are analyzed. Attention is paid to the internal laws of proverbial poetics. The author dwells on a peculiar artistic form of Lezgin proverbs and sayings, which is evidence of a high level of creative thinking, aesthetic taste, poetic perception of various spheres of life by the people. The relevance of the study is due to the fact that the issues of sound organization and the poetic form of the Lezgin folk proverbs and sayings have not yet become the object of comprehensive study. In this regard, the analysis of emotional and expressive means in small aphoristic genres of folklore is of great scientific interest. The goal of our work is to give an objective assessment of the peculiar poetic form of folk paremias, which is in the rhythmic organization, but our analysis does not pretend to a full interpretation of the topic under study. It is proved that the specificity of the artistic form of folk sayings is alliteration, rhyme, rhythm, sound repetitions that contribute to the poetic language of speech, the most clear expression of thoughts and the selection of the main meaning. A number of pictorial and expressive means of poetic speech helps her in this. Thus, rhythm and various kinds of rhymes contribute not only to the preservation of the unity of proverbs and sayings, but also to the selection of the main idea. The rhyme in folk proverbs plays a rhythmic and semantic role.Keywords: Lezgian folklore, small aphoristic genres of folklore, proverbs and sayings, alliteration, rhythm, rhyme, repetitions.DOI 10.18522/1995-0640-2020-1-46-52